HUBUNGAN ANTARA KECEMASAN DALAM MENGHADAPI MATA PELAJARAN MATEMATIKA DAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP 1 BANGUNTAPAN - Irma Aminatun; Agustina Sri Purnami (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
The purposes of this research is to know. 1) tendency of math anxiety, parental concern, and mathematics achievement, 2) correlation among math partially, and 3) relative contribution and effective contribution of each predictor. The subjects of this research is 112 students class 7th grade of junior high school 1 Banguntapan Bantul. Data collection techniques are questionnaires and test. The results showed that: 1) tendency of math anxiety is moderate, parental concern is high, and mathematics achievement is high, 2) there are: corelation positive among math anxiety and parental concern with mathematics achievement, corelation negative between math anxiety with mathematics achievement, and corelation positive between parental concern with mathematics achievement 3) relative contribution of math anxiety is 84,23%, relative contribution of parental concern is 15,77%, effective contribution of math anxiety and parental concern with mathematics achievement is 21,1%.